Stress distribution in the peri-implant area of pure titanium and titanium-zirconium small implants - Sabino, Tatiana de Andrade; da Silva-Concílio, Laís Regiane; Neves, Ana Christina Elias Claro; Claro, Ana Paula Rosifini Alves [UNESP]; Amaral, Marina; Vitti, Rafael Pino; Claro, Cristiane Aparecida de Assis (Universidade Estadual de Campinas, 2019)
Aim: In dental implant treatment, there is a demand for mechanically stronger implants. Despite the existence of several studies showing the clinical success of narrow diameter implants, most of them are based on pure titanium (cpTi) alloys. There is a few clinical evidences of the success rate of titanium-zirconium (TiZr) narrow diameter implants. The aim of this study was to evaluate the stress distribution in the peri-implant area of narrow diameter cpTi and TiZr implants under axial and oblique loads. Methods: Photoelastic models were produced using epoxy resin (PL2, Vishay Precision Group) from a master model. The implants (cpTi and TiZr; Straumann AG) had 3.3 mm in diameter and 12 mm in height. Loads of 100 N and 200 N were applied to the abutment at angles of 0° (axial), 10°, 20°, and 30° (oblique). A circular polariscope (Eikonal) was used under dark field white-light configuration. The isochromatic fringes were analyzed in the peri-implant region in 5 areas, using ASTM table with isochromatic fringes; cervical-mesial, cervical-distal, mid-mesial, mid-distal and apical. Results: In general, under axial and oblique loads, the stress in the TiZr implant was lower than in the cpTi implant. The load of 200 N produced the highest stress values in cpTi and TiZr implants. In both implants and loads, the fringes were located more in apical area at all angles evaluated. Conclusion: It can be concluded that for small implants, the load inclination and intensity change the pattern of stress distribution and the cpTi implant exhibited the highest peri-implant stress.
Keywords: Dental implants; Dental stress analysis; Mechanical; Stress